"Will Work for Maps": A History of the Library of Congress Geography and Map Division Special Map Processing Project. Issue 2 (30th June 2021) - Andrew, Paige G.; McElfresh, L. K.; Musser, L. R.
Abstract: After World War II, the Geography and Map Division at the Library of Congress acquired large quantities of military-related maps through the U.S. Army Map Service and similar military agencies, as well as from traditional domestic and foreign sources. The Division found itself in possession of many duplicates or otherwise expendable cartographic materials. The Division managed the surplus with its Special Map Processing Project. It recruited from the ranks of students, faculty, and librarians to secure hands-on staffing assistance with a kaleidoscopic variety of frontline projects. The Project served as a conduit to redistribute maps and other cartographic materials from their surplus collection. As the Division enjoyed the benefits of this arrangement — such as gaining control of their collections — many university, college, and other libraries benefited from acquiring duplicate materials, which strengthened, enlarged, and sometimes "seeded" map collections. The authors explore the Special Project's roots and founding; its structure, staffing, impacts, and outcomes; and important changes.